Large-Scale Synthesis of Carbon Dots Driven by Schiff Base Reaction at Room Temperature - Jifen Shi; Shuai Chang; Yating Gao; Jian Lv; Ruocan Qian; Binbin Chen; Dawei Li (Inorganics)
Photoluminescent carbon dots (CDs) have received increasing attention because of their admirable photophysical performances. The current strategies for synthesizing CDs typically require high energy consumption levels, and the ability to synthesize CDs at ambient temperature would be highly desirable. Herein, we design an energy-efficient approach to synthesize CDs through a Schiff base crosslinking between 2,5-dihydroxy-1,4-benzoquinone and tetraethylenepentamine at room temperature. The obtained CDs possess maximum photoluminescence (PL) emissions of 492 nm. Moreover, the proposed CDs possess good stability and a concentration-dependent PL and their maximum emissions can redshift from 492 to 621 nm as the CDs concentration increases. Because of their good luminescent properties, the CDs can be employed as optical probes for doxorubicin detection using the inner filter effect. This study develops a powerful approach for the large-scale synthesis of CDs with a superior performance.